Fatal Lung-Kidney Crosstalk in Bronchopulmonary Dysplasia: A Case of Refractory Weaning Unmasking Confirmed Williams Syndrome and Severe Obstructive Nephrolithiasis - Komang Okky Maharani Ciptana Putri; Mario Bernardinus Realino Nara; Defranky Theodorus (HM Publisher, 2026)
Background: Bronchopulmonary dysplasia (BPD) is the most common, serious morbidity of prematurity, frequently complicated by a protracted and difficult weaning process from respiratory support. Refractory weaning failure, defined as a lack of response to conventional BPD therapies, should trigger a broad investigation for non-pulmonary, systemic confounders. Case presentation: We present the case of a 1,480-gram, 35+4 weeks' gestation female infant with severe hyaline membrane disease who subsequently developed moderate-to-severe BPD. The infant exhibited refractory respiratory failure, failing multiple extubation attempts, and showing no clinical improvement despite standard BPD management, including a 15-day course of furosemide. On day 58, investigation for worsening cholestasis incidentally revealed a 1.3 cm obstructive right renal calculus with severe hydronephrosis and acute pyelonephritis. This finding, coupled with evolving